2023
DOI: 10.32604/cmc.2023.031325
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Crossover Operators for the Capacitated Vehicle Routing Problem

Abstract: We study the capacitated vehicle routing problem (CVRP) which is a well-known NP-hard combinatorial optimization problem (COP). The aim of the problem is to serve different customers by a convoy of vehicles starting from a depot so that sum of the routing costs under their capacity constraints is minimized. Since the problem is very complicated, solving the problem using exact methods is almost impossible. So, one has to go for the heuristic/metaheuristic methods and genetic algorithm (GA) is broadly applied m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…C. Krebs [29] is designed with two views, both the vehicle path view and the loading view, showing the corresponding task schedule and the position of each item in the cargo hold. Z. Hussain Ahmed [30] based on 8 crossover operators without any mutation operators are developed based on the three operations of selection, intersection and mutation in the genetic algorithm, and the results show that they have good solution results under a variety of sizes and different numbers of vehicle scales. None of the above studies take into account the time window requirements for the delivery process, which has stricter delivery time windows for electric meters.…”
Section: A Vehicle Routing Problems Within Urbanmentioning
confidence: 99%
“…C. Krebs [29] is designed with two views, both the vehicle path view and the loading view, showing the corresponding task schedule and the position of each item in the cargo hold. Z. Hussain Ahmed [30] based on 8 crossover operators without any mutation operators are developed based on the three operations of selection, intersection and mutation in the genetic algorithm, and the results show that they have good solution results under a variety of sizes and different numbers of vehicle scales. None of the above studies take into account the time window requirements for the delivery process, which has stricter delivery time windows for electric meters.…”
Section: A Vehicle Routing Problems Within Urbanmentioning
confidence: 99%
“…In [16], one simple genetic algorithm (GA) and four different hybrid GAs were proposed to solve the asymmetric distance-constrained vehicle routing problem (VRP). A set of eight crossover operators in genetic algorithms have been applied to the CVRP and a relative study among them is reported in [17]. A modified football game algorithm (MFGA) is proposed to solve the VRP with the time window in [18].…”
Section: Literature Reviewmentioning
confidence: 99%